The Thermal Stability of Tris(methimazolyl)borates and Their Germanium Complexes. Issue 15 (8th April 2014) - Wallace, Dawn; Chalmers, Kirsten; Dodds, Christopher A.; Stepek, Iain A.; Armstrong, David R.; Berlouis, Leonard E. A.; Reglinski, John; Spicer, Mark D.
Abstract: A series of methimazole‐based soft scorpionate anions ([RTm Me ] –, R = H, Ph, Me, n Bu) bearing substitution at the bridgehead boron have been used to produce a series of germanium complexes of general formulae [Ge(RTm Me )2 ]I2 . Structural analyses of the germanium complexes by X‐ray crystallography reveal that they all contain an octahedral S6 coordination sphere. The scorpionate anions (as their Li or Na salts) and their germanium complexes have been studied by thermogravimetric analysis. This analysis suggests that the degradation pathway for the free scorpionate anions differs from that of the complexes. Both pathways involve the loss of a methimazole ring thereby supporting the view that cleavage of the boron–nitrogen bonds can occur under thermally aggressive conditions. As expected, the presence of the germanium alters the degradation profile of the anion. In contrast to the free anions, the four complexes all display a similar mechanism for degradation. Although the presence of the germanium enforces a conformational change in the anions, its presence does not significantly increase the stability of the boron–nitrogen bonds. Abstract : A series of at‐boron substituted soft scorpionate ligands ([RTm Me ] – ) and their germanium(IV) complexes are reported and their thermal degradation explored. Two degradation pathways are observed; it is proposed that one involves alkyl migration (R = Me, n Bu) whereas the other pathway proceeds by heterocycle formation (R = H, Ph).